Coffee crop coefficient for precision irrigation based on leaf area index - Antonio Roberto Pereira (Bragantia, 2011)
Crop coefficient (Kc) for coffee plantations was found to be linearly related to the leaf area index (L) up to 3, i.e., Kc = b L. The basic assumption is that for irrigated trees the water use per unit leaf area (ET LA) is equal to the reference evapotranspiration (ETo) expressed also on a unit leaf area basis of the reference surface (ET LA = ETo/Lo). As recommended by FAO-56 the leaf area index (Lo) for the hypothetical reference surface (grass) is equal to 2.88, then the most likely value is b = Lo-1 = 2.88-1 = 0.347. However, for L > 3 (completely covered ground surface) Kc decreased from a peak value (~1.05) tending to an asymptotic low value around 0.7 for L > 6, but the linear model gives unrealistic Kc estimates; tentatively the empirical function Kc = 1.8 L-0.5 is offered here as an initial guess due to the lack of experimental results for the interval 3.5 <L < 5.5. To become operational under commercial fields it is necessary to estimate the leaf area per coffee tree (LA, m² tree-1), and based on a very limited set of data, LA was estimated as a function of planting density (PD, trees ha-1), i.e., LA = 88.38 - 8.63 Ln (PD). Alternatively, L (< 3.4) can be computed directly as a function of canopy volume (for V < 1.2 m³).